The CIMP Phenotype in BRAF Mutant Serrated Polyps from a Prospective Colonoscopy Patient Cohort. (9th April 2014) - Fernando, Winnie C.; Miranda, Mariska S.; Worthley, Daniel L.; Togashi, Kazutomo; Watters, Dianne J.; Leggett, Barbara A.; Spring, Kevin J.
Abstract : Colorectal cancers arising via the serrated pathway are often associated with BRAF V600E mutation, CpG island methylator phenotype (CIMP), and microsatellite instability. Previous studies have shown a strong association between BRAF V600E mutation and serrated polyps. This study aims to evaluate CIMP status of all the serrated polyp subtypes and its association with functionally important genes such as MLH1, p16, and IGFBP7 . CIMP status and methylation were evaluated using the real-time based MethyLight assay in 154 serrated polyps and 63 conventional adenomas. Results showed that CIMP-high serrated polyps were strongly associated with BRAF mutation and proximal colon. CIMP-high was uncommon in conventional adenomas (1.59%), occurred in 8.25% of hyperplastic polyps (HPs), and became common in sessile serrated adenomas (SSAs) (51.43%). MLH1 methylation was mainly observed in the proximal colon and was significantly associated with BRAF mutation and CIMP-high. The number of samples methylated for p16 and IGFBP7 was the highest in SSAs. The methylation panel we used to detect CIMP is highly specific for CIMP-high cancers. With this panel, we demonstrate that CIMP-high is much more common in SSAs than HPs. This suggests that CIMP-high correlates with increased risk of malignant transformation which was also observed in methylation of functionally important genes.